SDR technology application in the design of high-frequency noise signal generator - Trình, Thăng; Nguyễn Thế Duy (Journal of Military Science and Technology, 2023)
This article introduces the application of SDR technology in the design of noise signal generators in electronic warfare equipment, thereby researching and manufacturing short-wave interference generators using SDR technology.